Determinants of Households Tuberculosis Incidence in Arjasa Health Center of The Kangean Islands of Sumenep District - Trisno, Zetiawan (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2025)
Tuberculosis is a contagious infectious disease with the highest risk of transmission occurring in households or household contacts of sufferers. Puskesmas Arjasa Sumenep District is located in the Kangen Islands with the highest number of TB cases in a row in the last 3 years since 2021-2023. The purpose of this study was to analyze the determinants of household TB incidence in the Arjasa Puskesmas work area, Sumenep District. This type of research is observational analytic using case control research design. The population of this study was TB patients who were treated and registered at SITB totaling 134 TB patients while the sample was taken by cluster random sampling with a ratio of 1: 1 in cases and controls. The research sample of 92 patients consisted of a case group of 46 TB patients who came from household contacts of TB patients (cases) and a control group of 46 TB patients who were not from household contacts of TB patients. The results showed that knowledge (p value = 0.000; OR = 2,165), infection prevention behavior (p value = 0.000; OR= 3.233), perception (p value = 0.001; OR = 0,137), occupancy density (p value = 0.039; OR = 2.521), and air chang per hour (p value = 0.037; OR = 3,790) had a relationship with the incidence of positive household TB at the Arjasa Health Center, Kangean Islands, Sumenep District. Meanwhile, the wall and floor components of the room did not have a relationship with the incidence of positive household TB (p value > 0.05). Puskesmas Arjasa is expected to increase the strengthening of education to patients and families related to the importance of conducting infection transmission prevention behavior and providing better assistance to TB patients